Does Vocational Education Matter in Rural China? A Comparison of the Effects of Upper-Secondary Vocational and Academic Education: Evidence from CLDS Survey - Geng Wang; Xin Zhang; Rui Xu (MDPI AG, 2023)
The Chinese government has emphasised the role of vocational education and training (VET) in promoting the rural economy. Since 2018, the government has invested heavily in setting up secondary vocational schools, training centres, specialised programmes, and courses in rural areas. This paper aimed to explore whether VET at the upper-secondary level leads to better labour market outcomes than academic education in Chinese rural areas. We also aimed to quantitively investigate the social prestige of vocational and academic education among rural residents by comparing the subjective social status level of those who graduated from upper-secondary vocational schools and general academic schools. We drew data from the China Labour-force Dynamic Survey (CLDS). A binary logit model and multinomial logit model were used in this research. The results showed that rural upper-secondary vocational graduates had an advantage over general graduates in terms of their income and employment stability. However, VET led to lower subjective social status when compared with general education. This study demonstrated that although promoting VET in rural areas could potentially benefit rural residents financially, cultural change is needed to ensure the elevation of the standing of vocational education and promote the worthiness, effectiveness, and capabilities that vocational graduates possess.